(untitled) (Research, Society and Development, 2020)
Environmental education corresponds to the construction of essential values aimed at environmental conservation, quality of life and sustainability and must be present permanently throughout the educational level. This article has as specific objectives: to understand the need for environmental education and the awareness of its relationship with the health of all; Check the challenges of the search for new natural products for the composition of sunscreens that do not harm the ecosystem; And check the effectiveness of Lignin, a raw material derived from wood and its use in cosmetics and sunscreens. The research methodology in this article is based on an integrative review on the themes: environmental education, health and the efficacy and damage triggered by the use of traditional photoprotectors in the ecosystem, aiming to analyze the relationship between them. Solar radiation can have extremely harmful effects on the skin, antipfedas neoplasms and leading to early photoaging, however, through the proper use of sunscreens, we acquire one of the forms of photoprotection. Increasing evidence of the photodegradation of traditional organic sunscreens and the impact of their derivatives on the environment, food and the aquatic ecosystem as a whole, in addition to the possible penetration of these substances into the corneal extract of the skin, justify the research. For this reason, natural sunscreens are getting more and more attention. The records stem from work aimed at the development of new formulations and research of new photoprotective molecules, including lignin, an organic complex organic polymer found in the walls of plants, with potent action in the absorption of Ultraviolet light and a wide sun block, with good performance when to the associated spectra sunscreens.